2018
DOI: 10.18196/jmmr.7155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Clinical Pathway Typhoid Fever Monitoring at ABC Hospital Malang

Abstract: ABC Hospital has implemented 15 Clinical Pathway, and Typhoid Fever is the most cases that can be served. The inaccuracy of the monitoring report on the implementation of Clinical Pathway has prevented the hospital from taking appropriate actions to improve the implementation of Clinical Pathway Typhoid Fever. This study aims to determine the obstacles of monitoring implementation of Clinical Pathway Typhoid Fever in ABC Hospital. This research is a case study and descriptiveexplorative research, using documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
1
Order By: Relevance
“…The results of in-depth interviews with triangulation informants are in accordance with several previous studies where the implementation of clinical pathways can improve patient health outcomes, including the application of process aspects with integrated clinical pathways, it is hoped that service quality can be improved at affordable and predictable costs, as well as reducing patient readmissions at home sick (Shanti Rosalina et al 2018); Another study (Sena 2019) at Condong Catur Hospital found that the majority of patient outcomes before the implementation of the clinical pathway were in the cured category of 18 patients with a percentage of 90.0%, as well as the outcomes after CP implementation where 100% of the samples were in the cured category. The results of this in-depth interview are in line with the theoretical studies used in this study, namely a measure of the quality of health services can be seen from clinical outcomes that consider the success of all multidisciplinary aspects of care, related complications, rehabilitation, and recurrence experienced by patients for the same disease condition (Porter 2017 ).…”
Section: Table Conclusion Of Key Informant Analysis Matrix Related To...supporting
confidence: 84%
“…The results of in-depth interviews with triangulation informants are in accordance with several previous studies where the implementation of clinical pathways can improve patient health outcomes, including the application of process aspects with integrated clinical pathways, it is hoped that service quality can be improved at affordable and predictable costs, as well as reducing patient readmissions at home sick (Shanti Rosalina et al 2018); Another study (Sena 2019) at Condong Catur Hospital found that the majority of patient outcomes before the implementation of the clinical pathway were in the cured category of 18 patients with a percentage of 90.0%, as well as the outcomes after CP implementation where 100% of the samples were in the cured category. The results of this in-depth interview are in line with the theoretical studies used in this study, namely a measure of the quality of health services can be seen from clinical outcomes that consider the success of all multidisciplinary aspects of care, related complications, rehabilitation, and recurrence experienced by patients for the same disease condition (Porter 2017 ).…”
Section: Table Conclusion Of Key Informant Analysis Matrix Related To...supporting
confidence: 84%
“…Upaya perbaikan yang dapat dilakukan untuk mengatasi sampel pemeriksaan yang tertukar adalah dengan mewajibkan pemberian label oleh petugas kesehatan. Selain pemebrian label, sampel pemeriksaan juga dilakukan pendataan pada SIM RS guna mengintegrasikan diagnosis awal, sampel pemeriksaan, diagnosis akhir dan pelayanan yang diberikan serta mengurangi kemungkinan kejadian tertukarnya sampel pemeriksaan (14).…”
Section: Sampel Pemeriksaan Tertukarunclassified